“PLAN ESTRATÉGICO DE MARKETING PARA LA COMERCIALIZADORA DE VEHÍCULOS SANTIAGO MOTORS EN LA CIUDAD DE LOJA” - BRAVO PINZÓN, KEVIN ANDRES (2021)
The research project "Strategic marketing plan for the Santiago Motors vehicle marketer in the city of Loja" had as objectives the realization of a diagnosis of the current situation of the company and the realization of a proposal of a Strategic Marketing Plan for the Santiago Motors company from the city of Loja. The methods used were: deductive method, analytical method and synthetic method. The technique used to obtain the data was the survey, where three types of surveys were designed: one for potential clients with a total sample of 383 surveys; another for clients with a total sample of 156 surveys; 5 surveys applied to the company's employees; Additionally, an interview was conducted with the manager of the company. The surveys carried out with potential clients and clients of the Santiago Motors company, for pandemic reasons, were applied online through google forms. Once the information was obtained, it was continued with the tabulation of the same to later present it in tables and graphs with their respective analysis. Next, a diagnosis of the initial situation of the company was carried out; to continue with the external analysis where economic, technological, political and legal factors were addressed. Likewise, the analysis of Porter's 5 forces was carried out; a Competitive Profile Matrix where the competition was mainly identified; an ANSOFF Matrix for the identification of growth opportunities where the use of new marketing channels stands out. An EFE Matrix (Evaluation of External Factors) where the offer of substitute products, new sources of financing among others is highlighted as opportunities; while in the threats the economic situation of the country stands out above all, the high interest rates among other aspects. The EFI Matrix (Evaluation of Internal Factors) highlights as predominant strengths the geographical location of the company, the work team; and the Weaknesses highlight the lack of a formal structure, the inexistence of an institutional philosophy and a marketing plan. The summary of external and internal factors is also 5 shown in order to give way to the high impact SWOT matrix where it is mainly sought to take advantage of strengths and opportunities; and correctly face the weaknesses and threats raised. With this background, the discussion section was proposed where four strategic marketing objectives were proposed: first, the realization of a business philosophy that includes mission, vision and corporate values; second, provide an after- sales service; third, increase the visibility of the company in the market; and the fourth objective is to attract and retain new customers. This proposal seeks to mitigate and take advantage of the market to achieve a better sales performance and position of the company whose conclusions and recommendations thus highlight it.